Local Vibration Reduces Muscle Damage after Prolonged Exercise in Men - Anna Piotrowska (MDPI AG, 2021)
Prolonged exercise can lead to muscle damage, with soreness, swelling, and ultimately reduced strength as a consequence. It has been shown that whole-body vibration (WBV) improves recovery by reducing the levels of stress hormones and the activities of creatine kinase (CK) and lactate dehydrogenase (LDH). The aim of the study was to demonstrate the effect of local vibration treatment applied after exercise on the level of selected markers of muscle fiber damage. The study involved 12 untrained men, aged 21.7 ± 1.05 years, with a VO2peak of 46.12 ± 3.67 mL·kg−1·min−1. A maximal intensity test to volitional exhaustion was performed to determine VO2peak and individual exercise loads for prolonged exercise. The subjects were to perform 180 min of physical effort with an intensity of 50 ± 2% VO2peak. After exercise, they underwent a 60 min vibration treatment or placebo therapy using a mattress. Blood samples were taken before, immediately after the recovery procedure, and 24 h after the end of the exercise test. Myoglobin (Mb) levels as well as the activities of CK and LDH were recorded. Immediately after the hour-long recovery procedure (vibration or placebo), the mean concentrations of the determined indices were significantly different from baseline values. In the vibration group, significantly lower values of Mb (p = 0.005), CK (p = 0.030), and LDH (p = 0.005) were seen. Differences were also present 24 h after the end of the exercise test. The results of the vibration group compared to the control group differed in respect to Mb (p = 0.002), CK (p = 0.029), and LDH (p = 0.014). After prolonged physical effort, topical vibration improved post-workout recovery manifested by lower CK and LDH activity and lower Mb concentration compared to a control group.